Nigeria's economic diplomacy and development (Lagos, Nigeria : D.E.R. Ltd, 1993)
Many people do not know Nigeria beyond the status as the most populous country and the largest potential market in Africa. Dearth of appropriate information has been a major militating factor. This is the gap which this publication seeks to bridge.
Includes index
osc 8/11/2021
Ref
Keywords: Economic Development; Nigeria